1984
DOI: 10.1002/cne.902270113
|View full text |Cite
|
Sign up to set email alerts
|

Topographic organization of connections between the main olfactory bulb and pars externa of the anterior olfactory nucleus in the hamster

Abstract: The organization of connections between the main olfactory bulb (MOB) and pars externa (pE) of the anterior olfactory nucleus was studied in hamsters by using wheat germ agglutinin-horseradish peroxidase as both an anterograde and a retrograde neuronal tracer. Bulbar efferents of pE project exclusively to the contralateral MOB. A topographic organization is evident in these efferents, such that distinct sectors of pE project predominantly to certain sectors of the contralateral MOB and lightly to other sectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 58 publications
5
75
2
1
Order By: Relevance
“…In accordance with this hypothesis, Johnson et al demonstrated that sulfide-category odorants activate glomeruli at the ventro-caudal region in the ventral zone of the OB (19), and mitral/tufted cells in these regions project axons to the ventrocaudal region of the AONpE (11,18). sponses of ipsilateral AONpE neurons to contranostril inputs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In accordance with this hypothesis, Johnson et al demonstrated that sulfide-category odorants activate glomeruli at the ventro-caudal region in the ventral zone of the OB (19), and mitral/tufted cells in these regions project axons to the ventrocaudal region of the AONpE (11,18). sponses of ipsilateral AONpE neurons to contranostril inputs.…”
Section: Discussionmentioning
confidence: 85%
“…AONpE receives topographical axonal projections from the ipsilateral OB (11,(16)(17)(18), raising the possibility that the odorant category tuning of ipsinostril input to individual AONpE neurons is a result of the topography of afferent projection from the ipsilateral OB. In accordance with this hypothesis, Johnson et al demonstrated that sulfide-category odorants activate glomeruli at the ventro-caudal region in the ventral zone of the OB (19), and mitral/tufted cells in these regions project axons to the ventrocaudal region of the AONpE (11,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, superficial GCs might provide the means for lateral inhibition of tufted cells. Furthermore, because tufted and mitral cells show distinct patterns of axonal projections to the olfactory cortex (Skeen and Hall, 1977;Scott et al, 1980;Schoenfeld and Macrides, 1984), it is possible that GC subtypes that contact either mitral or tufted cells handle different aspects of odorant information. Given that tufted cells are adapted to detect low concentrations of odorants (Nagayama et al, 2004), we propose that early born GCs might preferentially regulate this function, whereas late born interneurons might rather control odorant identity by participating in the odor-specific temporal shaping of mitral cell spike responses.…”
Section: Sites Of Production and Migration Rates Of Newborn Neurons Amentioning
confidence: 99%
“…AON neurons project their axons as association fibers to the ipsi-OC, and to the contralateral (contra)-AON and contra-OC via the anterior commissure (AC) ( Fig. 1) (Schoenfeld and Macrides, 1984;Brunjes et al, 2005). It appears that the AON receives axonal inputs via the AC from the contra-AON or contra-OC (Haberly and Price, 1978), and thus receives sensory signals from both the ipsi-and contra-OEs (Wilson, 1997;Lei et al, 2006).…”
Section: Introductionmentioning
confidence: 99%